2017
DOI: 10.1164/rccm.201709-1821st
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Patients with Pulmonary Arterial Hypertension: A Blueprint for Action. An Official American Thoracic Society Statement

Abstract: At present, there are few studies that address health disparities in PAH. Given the potential adverse impact of health disparities, we recommend that research efforts be undertaken to address the topics discussed in the document. Awareness of health disparities will likely improve advocacy efforts, public health policy and the quality of care of vulnerable populations with PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 130 publications
(121 reference statements)
1
53
0
Order By: Relevance
“…Regardless, prior analysis using ZIP code analysis within the REVEAL registry showed that lower income groups had a longer time to disease recognition and that there were more functional class 3−4 patients in lower income groups at the time of diagnosis. 32 Black and Hispanic races were reported at a higher frequency in the lower 2 income categories compared with the higher 2 income categories. 32 Although these findings might suggest that outcomes should be worse in the black and Hispanic groups, this was not borne out in this analysis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Regardless, prior analysis using ZIP code analysis within the REVEAL registry showed that lower income groups had a longer time to disease recognition and that there were more functional class 3−4 patients in lower income groups at the time of diagnosis. 32 Black and Hispanic races were reported at a higher frequency in the lower 2 income categories compared with the higher 2 income categories. 32 Although these findings might suggest that outcomes should be worse in the black and Hispanic groups, this was not borne out in this analysis.…”
Section: Discussionmentioning
confidence: 87%
“…32 Black and Hispanic races were reported at a higher frequency in the lower 2 income categories compared with the higher 2 income categories. 32 Although these findings might suggest that outcomes should be worse in the black and Hispanic groups, this was not borne out in this analysis. It is unclear that adjusting for socioeconomic status Survival analysis limited to patients aged ≤ 60 years, using left truncation analysis.…”
Section: Discussionmentioning
confidence: 87%
“…These observations suggest that molecular, genetic, and environmental factors may all predispose AAs to PH and warrant further study to shed insight on PH pathophysiology or to identify at-risk individuals. 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, these observations need to be validated 1) in health and disease, 2) longitudinally, and 3) in other populations. Racial, ethnic and socioeconomic differences need further exploration (28,36,37). Normal values for RV function are needed for physiological modifiers of the normal RV in pregnant subjects and athletes, and the effects of processes such as puberty, menopause, and aging merit study.…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%